THE LEVEL OF CUSTOMER CONVENIENCE IN ACCESSING SERVICE FEATURES ON THE GOJEK APPLICATION - Martini, Tini; Azzahra, Hifia Alya; Nur Qolbi, Aprilia Eka; Surahman, Dongki; Susilawati Sugiana, Neng Susi (Jurnal Teknologi Informasi, 2025)
This study aims to determine the level of customer comfort in accessing service features on the Gojek application. As a widely used digital platform in Indonesia, Gojek offers a variety of services that demand an easy-to-use interface and smooth accessibility. This research uses a qualitative method involving 20 resource person who are active Gojek users. Data was collected through open-ended interviews to explore users' experiences, challenges, and satisfaction in accessing service features such as transportation, food delivery, payment systems, and customer support. The results show that most users find the Gojek application generally convenient and intuitive, especially in terms of navigation and feature integration. However, a minority of users expressed difficulties in accessing certain functions, especially during system updates or when using older phone models. Practical implications suggest that while Gojek's interface design is largely effective, there is still room for improvement in optimizing the user experience for a wider demographic, especially those less familiar with digital technology. Improving system responsiveness and providing clearer guidance within the application can increase customer satisfaction and loyalty. This study contributes to the ongoing importance of user-centered design in mobile applications.